2018
DOI: 10.1038/s41598-018-31717-7
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and arsenic attenuate canonical and non-canonical NLRP3 inflammasome activation

Abstract: Exposure to heavy metals can cause several diseases associated with the immune system. Although the effects of heavy metals on production of inflammatory cytokines have been previously studied, the role of heavy metals in inflammasome activation remains poorly studied. The inflammasome is an intracellular multi-protein complex that detects intracellular danger signals, resulting in inflammatory responses such as cytokine maturation and pyroptosis. In this study, we elucidated the effects of four heavy metals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…NLRP3 inflammasome activation is a multistep process that includes assembly of ASc and pro-caspase-1 (25). mtdNA from injured mitochondria has been reported to be fused in response to NLRP3 inflammasome activation (26,27). The results of the present study revealed that cORM-3 partially reversed the increase in mtdNA levels and the decreased mitochondrial integrity after HSR compared with icORM-3.…”
Section: Discussionmentioning
confidence: 45%
“…NLRP3 inflammasome activation is a multistep process that includes assembly of ASc and pro-caspase-1 (25). mtdNA from injured mitochondria has been reported to be fused in response to NLRP3 inflammasome activation (26,27). The results of the present study revealed that cORM-3 partially reversed the increase in mtdNA levels and the decreased mitochondrial integrity after HSR compared with icORM-3.…”
Section: Discussionmentioning
confidence: 45%
“…Another study demonstrated that arsenic enhanced the AIM2 inflammasome activation to increase IL-1 β/ IL-18 production 11 . In contrast, Ahn et al 15 demonstrated that arsenic could inhibit the activation of the NLRP3 inflammasome in macrophages in response to lipopolysaccharide treatment, which attenuated the elevation of serum IL-1β in mice. Animal and cell culture studies showed that arsenic trioxide and other arsenic compounds inhibited NLRP3 inflammasome, caspase-1, and IL-1β inflammatory signaling, and played a major role in its anti-cancer effects 43 .…”
Section: Discussionmentioning
confidence: 87%
“…One recent study reported that arsenic could activate the NLRP3 inflammasome and induce pyroptosis 14 . However, mercury and arsenic can inhibit interleukin (IL)-1β and IL-18 secretion, which is caused by the activation of both the classical and non-classical NLRP3 inflammasomes in macrophages, suggesting that exposure to these heavy metals could destroy the inflammasome-mediated immune responses and cause unexpected side effects 15 . Because of the inconsistency of these findings, the association between NLRP3 inflammasomes and arsenic exposure remains unclear.…”
mentioning
confidence: 99%
“…It is an essential source of pro-inflammatory factors and oxidative stress, such as TNF, interleukin and other neurotoxic substances [ 58 , 59 ]. Many studies showed that heavy metals could induce neurotoxicity via activating the microglial cells, especially Mn [ 22 , 23 , 62 ]. In vitro study demonstrated that Mn and/or LPS can activate BV2 cells via activating MAP kinase, PI3K/Akt pathways and inflammatory process [ 63 ].…”
Section: Discussionmentioning
confidence: 99%